Evaluation of the Knowledge of Primary Care Physicians About Important Nail Diseases Before and After a Short Online Training - Pauline Greco; Félix Pham; Gérard Duru; Xavier Lainé; Stéphane Dalle; Luc Thomas (Mattioli1885, 2023)
Introduction: Nail diseases are often diagnosed late with a potential prognostic and functional im-pact. This could be partly due to knowledge gaps among primary care physicians (PCPs). Objectives: To evaluate the knowledge about diagnosis and management of ten common/important nailconditions in a population of French PCPs and its improvement after a 31-minute online training session. Methods: We submitted 10 pre-test and post-test clinical cases and an educative online course on the diagnosis and the management of nail diseases to 138 volunteer PCPs; 73 completed the whole training path. Results: Compared to pre-test, more PCPs in the post-test required an urgent second opinion to der-matologist for pigmented melanoma (100% versus 80.3%; P <0.05) and use of inappropriate/danger-ous systemic treatment for trauma-induced nail changes was reduced after the training program (0% versus 6.8%; P <0.05).A lack of knowledge remained after training for amelanotic melanoma with an increase of mycological/bacteriological tests (9.6% versus 0%; P <0.05). Conclusions: Management of nail diseases by our panel of PCPs was suboptimal and was improved after a short online training.